Cavernous hemangioma of the nasal cavity: mimicking as the inverted papilloma - Panbude, Sushil Natthuji; Guha, Amrita Harish; Mahajan, Abhishek; Sable, Nilesh Pandurang; Arya, Supreeta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Cavernous hemangioma of the nasal cavity is extremely rare with only case reports in the literature highlighting the imaging findings on CT and MRI. Haemangioma are benign vascular tumours, which originate in the skin, mucosa and deep structures such as bones, muscles and glands. Exact etiopathogenesis of the haemangioma is not known, although they are divided into two types depending on the dominant vessel size at microscopy, capillary and cavernous. When these neoplasms arise in the nasal cavity, they are predominantly capillary and are found to arise from the nasal septum and are more common in the children. On the other hand, Cavernous haemangiomas are more likely to be found on the lateral wall of the nasal cavity and are more commonly seen in elderly. Also, inverted pappiloma also more commonly arise from the lateral wall of the nasal cavity, from the middle turbinate and also has the same demographics as the cavernous hemangioma. So, the distinction between the two should be carefully made based on the imaging findings so as to give the appropriate treatment to the patient. We have presented a rare case cavernous haemangioma arising from the mucosa of the middle nasal meatus, in a 37-year-old male which is mimicking as an inverted pappiloma based on the imaging features; however on histopathology proved to be cavernous hemangioma and also on the multimodal imaging that helps in early diagnosis and advocating appropriate and timely treatment.